An efficient calcium phosphate nanoparticle-based nonviral vector for gene delivery - Liu YC (Dove Medical Press, 2011)
Yachun Liu1,2,*, Tao Wang1,*, Fangli He1,*, Qian Liu1,*, Dexi Zhang2, Shuanglin Xiang1, Shengpei Su2, Jian Zhang11Key Laboratory of Protein Chemistry and Developmental Biology, Ministry of Education of China, College of Life Sciences; 2Key Laboratory of Chemical Biology and Traditional Chinese Medicine Research and Key Laboratory of Sustainable Resources Processing and Advanced Materials of Hunan Province, Ministry of Education of China, College of Chemistry and Chemical Engineering, Hunan Normal University, Changsha, Hunan, China*These authors contributed equally to this workBackground: Smaller nanoparticles facilitate the delivery of DNA into cells through endocytosis and improve transfection efficiency. The aim of this study was to determine whether protamine sulfate-coated calcium phosphate (PS-CaP) could stabilize particle size and enhance transfection efficiency.Methods: pEGFP-C1 green fluorescence protein was employed as an indicator of transfection efficiency. Atomic force microscopy was used to evaluate the morphology and the size of the particles, and an MTT assay was introduced to detect cell viability and inhibition. The classical calcium phosphate method was used as the control.Results: Atomic force microscopy images showed that the PS-CaP were much smaller than classical calcium phosphate particles. In 293 FT, HEK 293, and NIH 3T3 cells, the transfection efficiency of PS-CaP was higher than for the classical calcium phosphate particles. The difference in efficiencies implies that the smaller nanoparticles may promote the delivery of DNA into cells through endocytosis and could improve transfection efficiency. In addition, PS-CaP could be used to transfect HEK 293 cells after one week of storage at 4°C with a lesser extent of efficiency loss compared with classical calcium phosphate, indicating that protamine sulfate may increase the stability of calcium phosphate nanoparticles. The cell viability inhibition assay indicated that both nanoparticles show similar low cell toxicity.Conclusion: PS-CaP can be used as a better nonviral transfection vector compared with classical calcium phosphate.Keywords: transfection efficiency, particle size, protamine sulfate, stability